Participation of the Board of Basic Education Institutions in the administration of educational institutions under the Maha Sarakham Primary Educational Service Area Office 2 - Khamnin, Surat; Wongwatkasem, Wiralphat; Romsri , Suwattanapong (Journal for Developing the Social and Community, 2022)
The objectives were to study and compare the participation of basic education committees. in school administration Under the Maha Sarakham Primary Educational Service Area Office 2, classified by position and educational level. The sample group consisted of 263 members of the committee of external institutions and committees of internal schools. It was a 5-level estimation scale questionnaire with IOC values between 0.80-1.00 and the confidence level was 0.98. The basic statistics used to analyze the data were frequency, percentage, mean, standard deviation, and the statistic used for hypothesis testing were t-test and F-test. Research results Participation of the Board of Basic Education Institutions in school administration Under the Maha Sarakham Primary Educational Service Area Office, Region 2, it was at a high level both in overall and in each aspect. in general administration, followed by academics, while the aspect with the lowest average was budget. The opinions of the basic education committees on the participation of the basic education committees in school administration Under the Office of Maha Sarakham Primary Educational Service Area 2 with different positions There were statistically significantly different opinions at the .05 level, both overall and in each aspect. 3. The opinions of the basic education committees on the participation of the basic education committees in school administration under the Office of Maha Sarakham Primary Educational Service Area 2 with different educational levels There were no differences in opinions both in general and in each aspect.